PERIODIC SOLUTIONS FOR A DIFFERENTIAL EQUATION OF A RENEWABLE RESOURCE SUBJECT TO ADDITIVE ALLEE EFFECTS - Misganaw, Birku Demewoz (Journal of Global Research in Mathematical Archives(JGRMA), 2015)
Allee effect refers to reduction of individual fitness at low population densities. In this article we establish existence of positive periodic solutions for a model representing dynamics of a renewable resource which is subject to additive Allee effect. A fixed point theorem in cones has been employed to establish the existence of the periodic solutions.